2006
DOI: 10.1021/om0601551
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Elimination and Addition Reactions in Mixtures of Tri-n-Octyl Aluminum and 1-Dodecene

Abstract: Trialkyl aluminum compounds have been in commercial use for some time, and their reactions with simple alkenes have been studied in detail. In this paper, we present kinetic data at 95, 140, 150, and 160 °C for the neat liquid-phase reactions of tri-n-octyl aluminum and 1-dodecene, showing the emergence of octene, hexadecene, eicosene, and docosene isomers, as well as the isomerization of octenes and dodecenes. We used a comprehensive kinetic model and data from eight experiments to calculate four rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Chain termination is executed by classical terminal β-H elimination or induced by β-chain transfer to ethylene, forming the desired 1-alkenes ( k t ). Significant off-cycle reactions include 1,2-insertion of α-olefins followed by β-H elimination to form vinylidenes, chain walking followed by β-H elimination to form internal olefins, and 2,1-insertion followed by chain walking and/or β-H elimination to also form internal olefins …”
Section: Nonselective Ethylene Oligomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chain termination is executed by classical terminal β-H elimination or induced by β-chain transfer to ethylene, forming the desired 1-alkenes ( k t ). Significant off-cycle reactions include 1,2-insertion of α-olefins followed by β-H elimination to form vinylidenes, chain walking followed by β-H elimination to form internal olefins, and 2,1-insertion followed by chain walking and/or β-H elimination to also form internal olefins …”
Section: Nonselective Ethylene Oligomerizationmentioning
confidence: 99%
“…Significant off-cycle reactions include 1,2insertion of α-olefins followed by β-H elimination to form vinylidenes, chain walking followed by β-H elimination to form internal olefins, and 2,1-insertion followed by chain walking and/or β-H elimination to also form internal olefins. 17 Metal hydride intermediates have been isolated and characterized for aluminum-and nickel-based systems. A nickel hydride complex (Figure 1C), [{Ph 2 PCH 2 C(CF 3 ) 2 O}-NiH(PCy 3 )], was structurally characterized and found to insert ethylene to form the corresponding nickel ethyl complex, although further insertion was not observed.…”
Section: ■ Nonselective Ethylene Oligomerizationmentioning
confidence: 99%
“…Beginning with the first step (Reaction 1), Ziegler showed that α-olefins insert relatively rapidly into R 2 Al-H, and that the reaction goes to practical completion, whereas internal olefins insert much more slowly. 18 Other studies found likewise, 19 with one 20 showing that internal olefins insert around 200 times more slowly than α-olefins. The rate of insertion of internal olefins is one factor, but a related yet separate factor to consider is also the equilibrium position of this reaction.…”
Section: Introductionmentioning
confidence: 82%
“…The application derives the kinetic equations for all species (including intermediates) in the system and permits the user to determine which quantities will be part of the (Levenberg-Marquardt) nonlinear least-squares fitting procedure [8] to calculate rate constants and/or starting concentrations. (See [8,9] for details on the fitting strategy and descriptions of numerical integration methods.) For starting concentrations of the components, we used reported densities of 1-tetradecene, 1-hexadecene, and propionic acid to estimate molarities of each component in the starting mixtures.…”
Section: Kinetic Analysesmentioning
confidence: 99%